Pembuatan Tapai Ketan Putih: Making White Glutinous Tapai - Sitorus, Raya Uli; Toepak, Erwin Prasetya (Jurnal Jejaring Matematika dan Sains, 2022)
Glutinous tapai has a sweet and slightly sour taste and a distinctive taste because it contains alcohol, besides that the texture will be softer. Traditionally it takes 3-4 days to make white sticky rice tapai so that the tapai is sweet and soft. In the process of fermenting sticky rice will produce alcohol and CO2 (Carbon dioxide). White glutinous rice contains the most carbohydrates (79.40 g per 100 g of material) when compared to carbohydrates in cassava (34.7 g per 100 g of material. The greater the amount of glucose contained in an ingredient, the higher the amount of ethanol produced from the breakdown of glucose by the high amount of yeast (Saccharomyces cereviceae) in the tape that is made. . According to the results tapai has a slightly sweet taste with a slight alcoholic taste and a distinctive fragrant aroma. The texture is soft and watery and produces liquid which is the effect of the effect fermentation. Because the sweet taste of tapai is influenced by the sugar content of the tapai itself. The changes that occur are generally in accordance with the existing theory, the results of tapai are not optimal because the tapai still has a rather hard texture and does not have much water and taste which is not too sweet. This is because the fermentation time is short, which is only 3 days, and "the 3rd day of fermentation obtained low microorganism growth and the highest growth and height of microorganisms was the 9 day fermentation time"..